2010
DOI: 10.9744/ing.v11i2.17891
|View full text |Cite
|
Sign up to set email alerts
|

Questions and Questioning Techniques: A View of Indonesian Students’ Preferences

Abstract: This study investigated students' preference on teacher's questions and questionings techniques and more importantly on how they could facilitate or impede their learning. The results on teacher's questioning techniques showed that random nomination was more preferred than pre-arranged format nomination. In addition, techniques of nominating volunteering students and of giving wait-time were disliked by most student-respondents. As for types of question, the yes/no question was favored by most of the responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…In various classes, the employment of Bloom's taxonomy is vividly visible. Even though the display and convergent questions are dominant (David, 2007;Diaz et al, 2013;Hamiloğlu & Temiz, 2012;Ragawanti, 2009;Rahman & Manaf, 2017;Shomoossi, 2004;Sujariati, Rahman & Mahmud, 2016;Sunggingwati & Nguyen, 2013;Tofade et al, 2013;Yang, 2010), but the higher-order thinking questions are encouraged to develop and promote thinking. Researchers agreed that Bloom's taxonomy in questions is essential to encourage, extend and challenge students' abilities so that they think critically (Diaz et al, 2013;Klenn & Connell, 2004;Marzano et al, 2001).…”
Section: Cognitive Domain Of Bloom's Taxonomy In Questions To Promotementioning
confidence: 99%
See 1 more Smart Citation
“…In various classes, the employment of Bloom's taxonomy is vividly visible. Even though the display and convergent questions are dominant (David, 2007;Diaz et al, 2013;Hamiloğlu & Temiz, 2012;Ragawanti, 2009;Rahman & Manaf, 2017;Shomoossi, 2004;Sujariati, Rahman & Mahmud, 2016;Sunggingwati & Nguyen, 2013;Tofade et al, 2013;Yang, 2010), but the higher-order thinking questions are encouraged to develop and promote thinking. Researchers agreed that Bloom's taxonomy in questions is essential to encourage, extend and challenge students' abilities so that they think critically (Diaz et al, 2013;Klenn & Connell, 2004;Marzano et al, 2001).…”
Section: Cognitive Domain Of Bloom's Taxonomy In Questions To Promotementioning
confidence: 99%
“…Kira et al (2013) said that some questions should be asked in a certain level of students' intelligent ability so that the passiveness of students' response argued by Rahman and Manaf (2017) and Case (2013) as the unfortunate effect of Bloom's taxonomy higherorder thinking can be avoided. Moreover, David (2007) said that in the low order thinking, questions are very useful to engage classroom interaction, while Ragawanti (2009) added that uncomplicated required-answer of these questions made interaction in class more easily engaged. Moreover, Anderson et al (2001) found that low order thinking questions are important as the fundamental of higher-order thinking.…”
Section: Cognitive Domain Of Bloom's Taxonomy In Questions To Promotementioning
confidence: 99%
“…However, the teacher can also determine which student candidate will answer the questions that will be given by the teacher. The situation can be helpful to allow some time for students to think about and to present the answers (Ragawanti, 2010). In addition, students also sometimes cannot answer questions from the teacher.…”
Section: Introductionmentioning
confidence: 99%